Trisomy 21 screening based on first and second trimester in a Taiwanese population - Ruei-Yu Lan; Chen-Te Chou; Peng-Hui Wang; Ran-Chou Chen; Ching-Hua Hsiao (Elsevier, 2018)
Objective: This study investigates the performance of first- and second-trimester screening tests for detecting fetal trisomy 21 in a Taiwanese population. Materials and methods: This multicenter study 29,137 cases enrolled the chromosomal abnormality screening between 2013 and 2014 two years period from Taipei city. There were 23,990 was done the first trimester screening using a combination of fetal nuchal translucency, maternal serum β-human chorionic gonadotropin, and pregnancy-associated plasma protein-A between 11+0 and 13+6 weeks of gestation age. Second-trimester screening was done for 5149 cases using a double test (β-human chorionic gonadotropin and serum alpha fetoprotein) between 15 and 20 weeks of gestation. The cut-off risk for both is 1:270 or higher. Results: This multicenter study 29,137 cases that completed first- and second-trimester screening, and the outcome was available in 28,726 cases. The mean maternal age of the screen-positive group was 34.6 ± 4.2 years. The first-trimester had 891 cases screening positive with a detection rate of 97.5% for fetal trisomy 21, and false positive rate of 3.5%. In the second-trimester had 334 cases screening positive, the detection rate and false positive rate were 33.3% and 6.4% for trisomy 21, respectively. Conclusion: The first-trimester screening had higher performance with a lower false positive rate than the second-trimester screening. First-trimester screening could reduce the rate of unnecessary invasive testing for all pregnant women. Keywords: Down syndrome, First-trimester screening, Second-trimester screening